2021
DOI: 10.22449/0233-7584-2021-1-3-19
|View full text |Cite
|
Sign up to set email alerts
|

Soliton-Like Waves in the Vicinity of the Southern Kuril Islands

Abstract: urpose. This paper focuses on modulated solitons detected in time series of observational data on sea level oscillations in the Sea of Okhotsk, verifying the presence of nonstationary processes within a quantitative framework of methods. Methods and Results. The paper reports an analysis of wave observation data collected using ARW-type, bottom-mounted pressure sensors in the area of the Capes Castricum, Van-der-Lind and Lovtsova in the southern Kuril Islands. The time series obtained were bandpass filtered u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In [2], it was suggested that the wind solitons are one of the possible causes for the formation of rogue waves in a shallow sea. Frequent observation of solitons in the shallow sea zones was noted in [3]. In the shallow water, the impact of non-linear effects increases, which entails an increase in the run-up heights and leads to a destructive effect on the coast.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], it was suggested that the wind solitons are one of the possible causes for the formation of rogue waves in a shallow sea. Frequent observation of solitons in the shallow sea zones was noted in [3]. In the shallow water, the impact of non-linear effects increases, which entails an increase in the run-up heights and leads to a destructive effect on the coast.…”
Section: Introductionmentioning
confidence: 99%